Lexicographic Description of Maranao Language - Esconde, Gerlin Gay M (Journal of Social Work and Science Education, 2023)
One of the most significant local languages in Mindanao is the Maranao language. It has been featured in popular literary masterpieces of Mindaonaon and played an important part in its culture and history. Using a semi-structured interview guide, the researcher explored the existence of Filipino words in the Maranao language as well as comparing both languages in terms of structure and meaning through the interview conducted with three Maranao native language speakers. The objective of this study is to provide an example of the Maranao language’s overall lexicographic components, patterns and meanings. Results revealed that nouns, adverbs, adjectives, and verbs make up the majority of the researcher’s established Maranao terms collected during this examination. Additionally, “hard consonants” are aspirated in Maranao syllables, which enhance the sound of the vowels that follow. When it comes to words that are used in counting, the Maranao language, like all other languages, makes use of the technique of adding new words to the root words, which alters the meaning of the word and creates a different quantity or way of counting. In addition, words are stressed but in a way that creates a down step accent rather than a stress accent. Additional encouragements for writers, students, professors, and other language experts are required in order to use Maranao as a medium in education, literatures, publications, research, and many other sectors.